(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2021)
Background: Risk factors of PROM are not certainty known, but there have been several studies conducted to analyze the risk factors for the occurrence of PROM. PROM does not only affect the mother but also the baby who will be born. Babies born to mothers who have PROM are more at risk of developing birth asphyxia. PROM is suspected of causing infection in the mother which could result in birth asphyxia. Objective: To analyzing articles about the risk factors of PROM that caused birth asphyxia Method: Literature Review using the Systematic Literature Review (SLR) approach. Literature study by identifying, analyzing, through collecting existing data with a critical review process. Results: PROM can cause complications in mother and baby including post partum fever, wound infection, placental abruption and chorioamnionitis. While the side effects in infants are respiratory distress syndrome, asphyxia, septicemia, hyperbilirubinemia, meningitis pneumonia, and death in infants. PROM was also found to have an effect on causing birth asphyxia. The level of infection experienced by the mother, as indicated by the level of leukocytes in the blood, can help in preventing birth asphyxia. Conclusion: The risk factors of PROM that caused birth asphyxia is infection.